Mycorrhizae activity and diversity in conventional and organic apple orchards from Brazil - Purin S.* (2006)
The aim of this study was to characterize the impacts of a conventional, an organic apple orchard and a native grassland on the activity and diversity of arbuscular mycorrhizal fungi (AMF) located at the south of Brazil during winter and summer. AMF activity was measured by the mycorrhizal inoculum potential (MIP), mycorrhizal fungal hyphal length (HL), easily extractable and total Bradford-reactive soil protein (BRSP). AMF diversity was represented by richness, Shannon diversity index and number of spores. Orchards reduced the MIP of the soil and increased the HL when compared to the grassland site. The amount of easily extractable BRSP was not different among orchards and between seasons evaluated, with overall mean value of 1.23 mg g-1. However, the amount of total-BRSP was smaller in the conventional orchard (4.55 mg g-1) than in the organic orchard (4.91 mg g-1) and in the native grassland (5.12 mg g-1). T-BRSP and total organic carbon were strongly correlated in the grassland during the winter, suggesting the contribution of this protein for carbon stocks in the native soil of this region. The organic orchard presented the highest AMF richness, but sporulation and Shannon diversity index were larger in the conventional orchard. Our data suggest that the conventional orchard promoted higher impacts on the natural condition of AMF activity, being considered an unadvisable practice to soil conservation. © 2006 Elsevier Ltd. All rights reserved.